Обґрунтування потреб в оцінці фінансового стану підприємства, її необхідність і значення - Мелень, Олена Валентинівна; Торяник, Юрій Олександрович (НТУ "ХПІ", 2015)
В статті досліджено та проаналізовано поняття «фінансового стану»; розглянуто наукові погляди вітчизняних вчених щодо визначення сутності фінансового стану; досліджено необхідність аналізу фінансового стану підприємств в сучасних умовах; розкрито поняття комплексної оцінки фінансового стану підприємства; визначено основні завдання, методи та прийоми оцінки фінансового стану підприємства; розкриті особливості зовнішнього та внутрішнього фінансового аналізу, основні відмінності між ними.

In the article investigated and analyzed the concept of "financial state"; reviewed scientific views national scientists to determine the essence of the financial situation; investigated the need for analysis of financial standing of enterprises in modern conditions; The notion of a comprehensive assessment of the financial situation of the company; identified the main objectives, methods and techniques for assessing the financial state of the company; The features of external and internal financial analysis, major differences between them. The results of research can say that the stability of the financial state of the company depends on the accuracy and expediency of financial resources into assets, so it is necessary to examine first of all assess the composition and structure of assets and sources of its formation, and the reasons for their change. Particular attention is given to studying the causes that negatively affect the financial state, its liquidity and solvency.
Justification needs assessment of the financial condition of the company, its necessity and importance
Keywords: ліквідність; платоспроможність; стійкість фінансова; liquidity; solvency; financial stability